Factors associated with current and severe physical side‐effects after prostate cancer treatment: What men report. (10th October 2016) - Steentjes, L.; Siesling, S.; Drummond, F. J.; van Manen, J. G.; Sharp, L.; Gavin, A.
Abstract : We identified patient and disease characteristics associated with (1) "current" physical side‐effects of any severity; and (2) "severe" physical side‐effects "ever" experienced by 3, 348 (54%) prostate cancer (PCa) survivors in Ireland diagnosed 2–18 years previously. Postal questionnaires collected symptoms at diagnosis, post‐biopsy complications, comorbidities, primary treatments and physical side‐effects post‐treatment (urinary incontinence, erectile dysfunction, libido loss, bowel problems, breast changes, hot flushes, and fatigue, "ever" and "current" at time of questionnaire completion). Men were grouped by "early" (localised) and "late" (locally advanced/advanced) disease at diagnosis. Multivariable logistic regression analysis identified patient and disease‐related factors associated with post‐treatment side‐effects. Complications post‐biopsy were associated with higher risk of "current" libido loss and impotence. Radical prostatectomy was associated with higher risk of "current" and "severe" incontinence, libido loss and impotence in both early and late disease. In early disease, brachytherapy was associated with lower risk of "current" fatigue and "severe" impotence. Comorbidities were associated with higher risk of "current" experience of four side‐effects (incontinence, libido loss, bowel problems, fatigue). Men on active surveillance/watchful‐waiting reported lower risk of sexual dysfunction. These findings could inform development of tailored information on side‐effects, which, in turn, could inform treatment decision‐making and post‐treatment monitoring.